الظروف الجيولوجية والهيدروجيولوجية للجزء الجنوبي من سهل عكار - علي محمد الأسعد; غطفان عبد الكريم عمار; شريف بدر حايك (Tishreen University, 2019)
تقع منطقة البحث في الجزء الجنوبي لمشروع سهل عكار. يحدها من الجنوب نهر الكبير الجنوبي عند الحدود اللبنانية، و من الشمال نهر الأبرش، و يحدها من الشرق تلال الصفصافة و كرتو، ومن الغرب البحر المتوسط. يهتم البحث بدراسة الظروف الجيولوجية و الهيدروجيولوجية للمنطقة المدروسة، تحت تأثير استثمار شبكات الري و الصرف, ووضع خطة استثمارية رشيدة لموارد المياه الجوفية فيها. تتغيرقيم الناقلية المائية للطبقات الحاملة للمياه الجوفية في منطقة البحث ضمن حدود كبيرة (5000-15 ) م2 / يوم. تبعاً لتنوع التوضعات الجيولوجية و تغير خصائصها الرشـحية، الأمر الذي أدى إلى تغيرات ملحوظـة لأعماق الميـاه الجوفيـــة ( تصل إلى 6 م ) في آبار شبكة الرصـد خلال فتـرة المراقبـة و التي استمرت ثلاثة أعوام ( منذ شهر تشرين الأول 1999). كما تقل أعماق المياه الجوفية في غالبية آبار شبكة الرصد، بسبب زيادة التغذية الراشحة من الهطولات المطرية و من مياه شبكات الري بعد البدء باستثمارها منذ عام، وذلك بعد توقف معظم المزارعين عن استخدام المياه الجوفية لأعمال الري. إن المياه الجوفية في منطقة البحث صالحة للاستخدامات المختلفة وهي سهلة الاستثمار.   The area of this research is located in the southern part of Akkar Plain Project. It is limited by Al-Kabir Al-Janoubi River from the south, Al-Abrash River from the north, the hills of Safsafeh and Karto from the East, and the Mediterranean Sea from the west. The research studies the geological and hydrogeological conditions of the area of the study under the effects of irrigation and sewerage network . the research will put comprehensive exploitation plan for groundwater resources. The values of transmissivity of aquifers in the research area vary along a wide range (15 - 5000) m2/day depending on the geological deposits and the changes of their infiltration characteristics. That leaded to changes in the depths of groundwater (up to 6 m) within the wells of monitoring network during the observation period that lasted for three years (from October 1999). The depths of ground water decrease in most of the wells of the monitoring network because of the increase in the infiltration from rainfalls and water of irrigation networks after the beginning of exploitation that started from one year, after most farmers had stopped the use of groundwater for irrigation works. Groundwater in the research area is valid for various uses and easily exploitations.